Metode Pembelajaran Sekolah Dasar di Sd Negeri 023900 Binjai Utara - Zywetta, Aurora; Zahara, Latifah; Saudia, Nadhira Al; Harahap, Nurul Hasanah; Ritonga, Yulinda (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Education is a key element in human resource development, and good education will produce good human resources. In this regard, educators have an important role in educating the younger generation to be virtuous, intelligent and devoted to God Almighty. Thus, learning methods play an important role in the learning process. Learning methods help teachers achieve predetermined learning goals. The purpose of this writing is to find out the learning methods used at SD Negeri 023900 North Binjai. This research method uses a qualitative approach and involves literature study methods. Data collection techniques use interview and literature research methods. The results found in this research include 2 results, namely; (1) Learning methods applied at SD Negeri 023900, (2) Advantages and disadvantages of the learning methods applied.